Dispensatorium Parvum (al-Aqrābādhīn al-saghīr) - Ibn-Sahl, Sabur; Kahl, Oliver (Leiden ; Boston : BRILL, 1994)
This book comprises a philological analysis and critical edition of an undated, anonymous Arabic pharmacopoeia, preserved in the form of a unique manuscript. A study of the manuscript showed that it represents the oldest hand-written witness of Arabic pharmacology known to date, and one of the earliest pharmacopoeias ever written in Arabic, viz. the small, and authentic version of an otherwise lost or, in the course of transmission, largely transmuted Aqrābādhīn originally composed by the Christian physician Sābūr b. Sahl (d. 255/869). Following a brief introduction, the manuscript is described, analysed and illustrated by ten facsimiles. A biographical sketch of the author is followed by a critical edition of the manuscript. Philological observations, a glossary of technical terms, and indices are appended to the edition.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Medicine, Arab; Pharmacy -- Early works to 1800.; Pharmacy; Medicine, Arabic; Médecine arabe; Medicine, Arab; Pharmacy; Early works